Etyczne oblicza dyplomacji .......... 19 - Czubik, Agnieszka (Oblicza dyplomacji, 2025)
THE ETHICS OF DIPLOMACYThis study discusses the relationship between ethics and diplomacy. The tasks facing contemporary diplomacy in the context of the functioning of the international community were investigated. The analysis of the functions of foreign service was preceded by a discussion of the evolution of the tasks of diplomacy from a historical perspective. Three basic stages, important for the development and formulation of the concept of diplomatic activities justified by the interests of the international community were distinguished, namely diplomacy in the interest of “the prince”, diplomacy in the interest of the state (raison d’etat), and diplomacy aimed at protecting the international order (raison de systeme). Diplomacy acting in the name of raison de systeme may be implemented in the forum of international organizations, but also by individual states or groups of states. It will then take the form of cosmopolitan diplomacy acting for the sake of the international order and for the protection of the international community, which does not exclude, and sometimes conditions, actions in the name of the raison d’etat undertaken to protect the state and its citizens.